On certain sequence spaces II - Hüsnü Kizmaz (International Journal of Mathematics and Mathematical Sciences)
In this paper we define the space co(Δ)={x=(xk)/xk−kk−1→0(k→∞),xo=0,xk∈ℂ} and compute its duals (Continuous dual, β-dual and N-dual) The aim of this paper is to give same results about matrix mapping of co(Δ) into other sequence spaces including the convergent sequences, null sequences and bounded sequences.